PARENTAL INVOLVEMENT OF INDONESIAN SENIOR HIGH STUDENTS: CONTRIBUTION TOWARDS ACADEMIC SUCCESS - Rasyid, Fathor (JL3T (Journal of Linguistics, Literature and Language Teaching), 2017)
The research was carried out to investigate whether there was any significant contribution of family background and parental involvement towards students’ achievement, and which spesific parental involvement aspects best predict students English performance. To this end, English test was administered to Indonesian senior high school students (n= 222), and questionnaire was to their parents.Path analysis with smartPLS was utilized to analyze the data. The results revealed that the contribution of family background towards parental involvement is significant. However, there are no significant contributions of parental involvement and family background towards students’ achievement. No significant contribution is also found between family background and students’ achievement through intermediary variable of parental involvement. Other finding indicated that parents’ aspiration and expectation along with enhancing learning opportunities at home had the strongest effects on students’ achievement.